Biosynthesis and characterization of silver nanoparticles using ecoenzyme as reducing agent - Ratna Dewi Eskundari; Agus Purwanto; Erliana Putri Isnanto; Muthia Zakiyyatus Sabrina (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
Silver nanoparticles have recently become one of the nanomaterials that are widely developed as antibacterial agents because they have a broad spectrum of activity against both Gram-positive and Gram-negative bacteria. This study aimed to synthesize silver nanoparticle using ecoenzyme solution as a reducing agent and to characterize its characters. This study was conducted in two main stages, i.e. biosynthesis which was carried out by reacting ecoenzyme solution with silver nitrate solution, and the next stage was the characterization of silver nanoparticle, including morphological analysis using spectrophotometer, scanning electron microscope (SEM), and particle size analyzer (PSA) as well as analysis of antibacterial activity. The results showed that silver nanoparticles were successfully synthesized. Morphological analysis using SEM showed that silver nanoparticles were cubic, rectangular, or spherical, while the size analysis was around at 83.64 nm, although visually, there were no visible color change to dark brown and no peak at a wavelength of 400-600 nm. Antibacterial activity analysis showed that ecoenzyme-derived silver nanoparticles had the ability to inhibit both gram-positive and gram-negative bacteria, and specifically had better antibacterial properties for gram-positive bacteria compared to the control. These results indicated that silver nanoparticle using ecoenzyme as bioreductor has the potential to be used as antibacterial agents for multidrug-resistant bacterial infections.